IMPLEMENTASI PENILAIAN OTENTIK DALAM MATA PELAJARAN BAHASA INDONESIA DI SMP NEGERI KABUPATEN PESISIR SELATAN - Hasanah, Mutya; Atmazaki, Atmazaki; Abdurahman, Abdurahman (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACT The purpose of this study is to describe (1) types of authentic assessment used teachers in Indonesia language subjects in junior high Country South Pesisir Regency, (2) conformity assessment between teacher done authentic language subjects Indonesia in SMP Negeri South Pesisir Regency and theory on the curriculum of 2013, and (3) constraints faced by teachers Indonesia language subjects in junior high Country South Pesisir Regency in conducting assessment authentic. This type of research is qualitative research with a descriptive method. This research was conducted at the JUNIOR HIGH SCHOOL South Pesisir Regency Country i.e. SMP 1 Painan, SMP 2 Painan, and SMP 1 Tarusan. The data in this study is the result of collecting data about the understanding and implementation of assessment authentic conducted Indonesia language teacher in junior high Country South Pesisir Regency which is obtained from the data source. Techniques employed i.e. observation, interviews, and documentation study. A technique used to analyze the data, namely the identification data, data presentation, and the withdrawal of the conclusion. Based on the findings of the research and the discussion can be summed up in the following three things. (1) the overall types of authentic assessment has been used by Indonesia language teacher in junior high Country South Pesisir Regency. (2) the overall alignment of authentic assessment done guru Indonesia language subjects in junior high Country South Pesisir Regency and the theory on Curriculum 2013 is already good. Kata kunci: implementasi, bahasa Indonesia